Intermediate Structures of Nucleation and Growth during Solidification of CuO Constrained by Graphene. Issue 7 (17th February 2020) - Ge, Mengke; Yuan, Wenjuan; Zhou, Lingling; Deng, Ziliang; Hu, Min; Li, Xiang; He, Jia; Xi, Wei; Luo, Jun
Abstract: Important solid‐state information regarding solidification remains unknown, such as the intermediate structure before nucleation and precipitation pathways for each component in multicomponent materials during crystal growth. Herein, a unique intermediate structure with unequal lattice structure (the main performance is the curved lattice fringes and the unequal interplanar spacing) is observed in situ at the atomic level before CuO nucleation. The results of experiments and molecular dynamics simulations indicate that the formation of this intermediate may be due to the irregular agglomeration of Cu and O atoms. During growth, Cu–Cu layers repeatedly form at the solid–liquid interface as an intermediate state, then oxidizes, and finally forms a perfect CuO crystal. These results help to reveal the mystery of nucleation nanomaterials, especially the multicomponent materials, and elucidate microscopic crystal growth mechanisms during multicomponent materials solidification. Abstract : Intermediate structures are observed in situ at the atomic level during CuO droplet nucleation and growth. The unique intermediate structure with nonuniform interlayer spacing forms because of the irregular agglomeration of Cu and O before nucleation. An intermediate structure of two Cu layers possibly forms at the solid–liquid interface during growth.